2014
DOI: 10.1371/journal.pone.0105307
|View full text |Cite
|
Sign up to set email alerts
|

Methylglyoxal Induces Systemic Symptoms of Irritable Bowel Syndrome

Abstract: Patients with irritable bowel syndrome (IBS) show a wide range of symptoms including diarrhea, abdominal pain, changes in bowel habits, nausea, vomiting, headache, anxiety, depression and cognitive impairment. Methylglyoxal has been proved to be a potential toxic metabolite produced by intestinal bacteria. The present study was aimed at investigating the correlation between methylglyoxal and irritable bowel syndrome. Rats were treated with an enema infusion of methylglyoxal. Fecal water content, visceral sensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 45 publications
0
21
0
Order By: Relevance
“…These results suggested that the model of IBS-D was established successfully. 29,31 After the treatment, the wet feces weight, total number of fecal pellets and fecal water content in the FLCWK group, and the pinaverium bromide group were reduced more than that in the NMS + RS group (n = 8, wet feces weight: drug groups: P < 0.05; total number of fecal pellets: high dose group, middle dose group, pinaverium bromide group: P < 0.01, low dose group: P < 0.05; fecal water content: high dose group, middle dose group, pinaverium bromide group: P < 0.01, low dose group: P < 0.05). Furthermore, there was no statistical difference in fecal indexes between the drug groups and the NH group (n = 8, P > 0.05), except the low dose group (n = 8, total number of fecal pellets: P < 0.05; fecal water content: P < 0.05).…”
Section: Effect Of Fengliao-changweikang On Fecal Indexes In Diarrheamentioning
confidence: 99%
“…These results suggested that the model of IBS-D was established successfully. 29,31 After the treatment, the wet feces weight, total number of fecal pellets and fecal water content in the FLCWK group, and the pinaverium bromide group were reduced more than that in the NMS + RS group (n = 8, wet feces weight: drug groups: P < 0.05; total number of fecal pellets: high dose group, middle dose group, pinaverium bromide group: P < 0.01, low dose group: P < 0.05; fecal water content: high dose group, middle dose group, pinaverium bromide group: P < 0.01, low dose group: P < 0.05). Furthermore, there was no statistical difference in fecal indexes between the drug groups and the NH group (n = 8, P > 0.05), except the low dose group (n = 8, total number of fecal pellets: P < 0.05; fecal water content: P < 0.05).…”
Section: Effect Of Fengliao-changweikang On Fecal Indexes In Diarrheamentioning
confidence: 99%
“…Concentrations in the same range as those used in our report (higher than 100 μM MG) were used in recent in vitro studies investigating the effects of MG on ion channels and transporters (Ohkawara et al, ; Quadri et al, ; Yang et al, ) and in experiments carried out on isolated rat thoracic aorta (Mukohda et al, ). In the bowel, the relevant concentrations could be even higher than the ones used in this work (Zhang et al, ).…”
Section: Discussionmentioning
confidence: 69%
“…MG can also be synthesized from dihydroxyacetone phosphate by anaerobic bacteria that colonize the gastrointestinal tract (Baskaran et al, ), and under these circumstances MG may induce irritable bowel syndrome (Zhang et al, ). Dietary MG (e.g., from mānuka honey) is degraded in the intestine (Degen et al, ).…”
mentioning
confidence: 99%
“…MGO produced by intestinal bacteria is reported as a potential toxic metabolite involved in many gut diseases, including functional constipation . Moreover, microbiomes of functionally constipated individuals show a lower abundance of genes involved in MGO degradation compared with healthy microbiomes . Together, these studies point to MGO being a toxic metabolite in gut diseases.…”
Section: Discussionmentioning
confidence: 92%